Acoustic and visual stimuli combined promote stronger responses to aerial predation in fish. (19th July 2021) - Lukas, Juliane; Romanczuk, Pawel; Klenz, Haider; Klamser, Pascal; Arias Rodriguez, Lenin; Krause, Jens; Bierbach, David
Abstract: Bird predation poses a strong selection pressure on fish. Since birds must enter the water to catch fish, a combination of visual and mechano-acoustic cues (multimodal) characterize an immediate attack, while single cues (unimodal) may represent less dangerous disturbances. We investigated whether fish could use this information to distinguish between non-threatening and dangerous events and adjust their antipredator response to the perceived level of risk. To do so, we investigated the antipredator behavior of the sulphur molly ( Poecilia sulphuraria ), a small freshwater fish which is almost exclusively preyed on by piscivorous birds in its endemic sulfide spring habitat. In a field survey, we confirmed that these fish frequently have to distinguish between disturbances stemming from attacking birds (multimodal) and those which pose no (immediate) threat such as bird overflights (unimodal). In a laboratory experiment, we then exposed fish to artificial visual and/or acoustic stimuli presented separately or combined. Sensitivity was high regardless of stimulus type and number (more than 96% of fish initiated diving), but fish dove deeper, faster, and for longer when both stimuli were available simultaneously. Based on the system's high rates of bird activity, we argue that such an unselective dive initiation with subsequent fine-tuning of diving parameters in accordance to cue modality represents an optimal strategy for these fish to save energy necessary to respond to future attacks. Ultimately, our study shows that fish anticipate the imminent risk posed by disturbances linked to bird predation through integrating information from both visual and acoustic cues. Abstract : When fish are attacked by birds from outside the water, visual and olfactory cues are often distorted or inaccessible. However, additional cues like sound of the attack impact become available. In our experiments, fish responded strongest with diving when visual cues from above-surface movement and an impact sound were perceived simultaneously. Each cue alone might not be sufficient to indicate a bird's attack, but combined, fish may identify the disturbance as an immediate threat.